Hematoporphyrin-based photodynamic therapy for cutaneous squamous cell carcinoma in cats - Ferreira, Isabelle [UNESP]; Rahal, Sheila Canevese [UNESP]; Rocha, Noeme Sousa [UNESP]; Gouveia, Ana H.; Correa, Thais P. [UNESP]; Carvalho, Yuri K. [UNESP]; Bagnato, Vanderlei S. (Wiley-Blackwell Publishing, Inc, 2009)
Photodynamic therapy (PDT) using a haematoporphyrin derivative (Photogem (R), General Physics Institute and clustes Ltda) as photosensitizer and light emitting diodes (LEDs) as the light source was evaluated in 12 cats with cutaneous squamous cell carcinoma. Lesions were illuminated with LEDs, (300 J/cm for 30 min) 24 h after the administration of the photosensitizer. Clinical responses were classified as complete disappearance of the tumour with total re-epithelialization; partial response (a reduction greater than 50%); and no response (less than 50% reduction). Tumours localized to the pinna treated with one (n = 3) or two (n = 4) applications of PDT yielded no response. Highly invasive tumours of the nose and nasal planum also showed no response, after two treatments (n = 2). A combination of PDT and surgery was performed in three cases. Two cats showed partial response and one complete response with one application of therapy 30 days after nasal surgery. Small and noninfiltrative lesions (n = 3) of the nasal planum showed a PR with one application (n = 2) and a CR with two applications (n = 1). This study shows that PDT using Photogem (R) and LEDs can provide local control of low-grade feline squamous cell carcinoma. The addition of PDT to surgery in more invasive cases may help prevent recurrence.